Barriers to Use of Refractive Services in Mozambique. Issue 1 (January 2015) - Thompson, Stephen; Naidoo, Kovin; Gonzalez-Alvarez, Carmen; Harris, Geoff; Chinanayi, Farai; Loughman, James
ABSTRACT Purpose Uncorrected refractive error remains a leading cause of visual impairment (VI) across the globe with Mozambique being no exception. The establishment of an optometry profession in Mozambique that is integrated into the public health system denotes significant progress with refractive services becoming available to the population. As the foundations of a comprehensive refractive service have now been established, this article seeks to understand what barriers may limit their uptake by the general population and inform decision making on improved service delivery. Methods A community-based cross-sectional study using two-stage cluster sampling was conducted. Participants with VI were asked to identify barriers that were reflective of their experiences and perceptions of accessing refractive services. A total of 4601 participants were enumerated from 76 clusters in Nampula, Mozambique. Results A total of 1087 visually impaired participants were identified (884 with near and 203 with distance impairment). Cost was the most frequently cited barrier, identified by more than one in every two participants (53%). Other barriers identified included lack of felt need (20%), distance to travel (15%), and lack of awareness (13%). In general, no significant influence of sex or type of VI on barrier selection was found. Location had a significant impact on the selection of several barriers. Pearson χ2 analysis indicated that participants from rural areas were found to feel disadvantaged regarding the distance to services (p ⩽ 0.001) and adequacy of hospital services (p = 0.001). Conclusions For a comprehensive public sector refractive service to be successful in Mozambique, those planning its implementation must consider cost and affordability. A clear strategy for overcoming lack of felt need will also be needed, possibly in the form of improved advocacy and health promotion. The delivery of refractive services in more remote rural areas merits careful and comprehensive consideration.